THE ROLE OF AGRICULTURAL AGENTS MANAGEMENT OF AGRICULTURAL INNOVATIONS KNOWING IN IMPROVING FILED EXTENSION ACTIVITIES IN THE CENTRAL REGION PROVINCES OF IRAQ. - & SALMAN, KAREM (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This research aims at achieving the following goals:- the first one is to Identify the actual management of the agricultural agent in knowing the agricultural innovations represented by the following (knowledge diagnosis, the acquiring and generating of knowledge, knowledge updating, knowledge planning, knowledge application publishing and sharing of knowledge, organizing and storing knowledge, knowledge observation). The second one is to identify the role of knowledge management of agricultural agent in improving the extension and field activities, the next one is to find out the relation between the aspects of the role of management of agricultural agent in knowing the agricultural innovation with improving the extension activities as well as identifying the barriers that prevent the application of the management of agricultural agent in knowing the agricultural innovation according to the agricultural extension point of view.The population of the study includes the central provinces of Iraq consisting of (8) ones. A sample was taken randomly on rate of (%50) the provinces are (Baghdad, Najaf, Karbala, Babylon) (564)ones. The random graded proportional (%40) sample was taken from the agricultural agent distributed on the previous provinces they one (564) ones (134) for each province. In order to achieve these goals, a questionnaire has been prepared to collect the data from the agricultural agent. The questionnaire consists of (101) items distributed over three aspects (65) items in the field of agricultural agent management in knowing the agricultural innovations distributed over (8) aspects. (23) items for improving the extension activities and (13) items for the obstacles that prevent the application of agricultural innovations knowledge. The researcher has reached to the following results:--The knowledge diagnosis process in knowing the agricultural innovation is regarded one of the most important demand to achieve the extension activities and it also takes number because of its importance by the agreement of the researchers. The probable mean amount is (3,14) and the percentage weight is (78,7) while knowledge organizing takes last position according to the researchers by probable mean amount (3,27) and percentage weight (%87,75). -There is a correlation and statistical relation between the management of the agricultural agent in knowing the agricultural innovations and improving the extension activities. The researcher has recommended the following:The importance of raising the level of knowledge management application in instructional organizations by giving the agricultural agent more authorizations which ensure the application of their knowledge in the instructional field.The researcher has also recommended to establish an administrates units to organize the effort of knowledge management in the instructional organizations and it should be independent and have a connection with senior management it could be joined to the management of developing administration department as well as it should be qualified by experts and the agricultural agent should be qualified in technical field through enroll them in training courses according to their needs and the requirements of the instructional work.